Pengetahuan dan Sikap Remaja tentang Mitigasi Bencana Hidrometeorologi melalui Program SABAR di Sungai Iyu Kecamatan Bendahara Aceh Tamiang - Sitohang, Nur Asnah; Asiah, Nur; Oktari, Rina Suryani (Jurnal Riset Hesti Medan, 2023)
Indonesia is a country with the second largest level of disaster vulnerability in the world after Bangladesh. Almost every year disasters occur in Indonesia. Indonesia, as a disaster-prone country, must have volunteers who are able to provide services to reduce disaster risks. These volunteers have a big role in reducing the risk of disasters. Nurses in providing disaster nursing services can go through programs to increase community resilience. The natural flood disaster that Aceh Tamiang residents just experienced occurred in November 2022. Sungai Iyu Village is one of the areas affected by flooding. The location of SMP Negeri 1 was flooded to a height of 1.5 meters. So the learning process had to be stopped. People took refuge on the side of the road which was safe from flooding. There is no permanent community gathering point yet. The aim of the research is to identify the knowledge and attitudes of SMPN 1 Bendahara students regarding disaster mitigation before and after the SABAR Program training. The aim of the research is to identify the knowledge and attitudes of SMPN 1 Bendahara students regarding disaster mitigation before and after the SABAR Program training. The research design that has been used is descriptive. The sampling technique is purposive sampling. The data analysis that has been used is univariate. The majority of research results regarding adolescent knowledge before the SABAR program training was sufficient (51.4%) and good (24.3%), after training it was sufficient (27%) and good. The majority of teenagers' attitudes before the training agreed (54.1%) and strongly agreed (24.3%) and after the training agreed (51.4%) and strongly agreed (45.9%). Research proves that the SABAR training program can increase teenagers' knowledge and attitudes towards hydrometeorological disaster mitigation.